2004
DOI: 10.1212/01.wnl.0000130250.62842.c9
|View full text |Cite
|
Sign up to set email alerts
|

Self-treatment of benign paroxysmal positional vertigo

Abstract: Abstract-The authors compared the efficacy of a self-applied modified Semont maneuver (MSM) with self-treatment with a modified Epley procedure (MEP) in 70 patients with posterior canal benign paroxysmal positional vertigo. The response rate after 1 week, defined as absence of positional vertigo and torsional/upbeating nystagmus on positional testing, was 95% in the MEP group (n ϭ 37) vs 58% in the MSM group (n ϭ 33; p Ͻ 0.001). Treatment failure was related to incorrect performance of the maneuver in the MSM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 15 publications
4
76
1
4
Order By: Relevance
“…So, if the 180° swing is performed quickly enough, then the effect on the posterior canal can be equivalent to a slow backward rotation. The success of the Semont manoeuvre therapy for BPPV is known to depend critically on the speed of the 180° whole-body swing [Radtke et al, 2004]. Analyses of the accelerations acting on the SCC during the Semont manoeuvre suggest that the optimum duration of the 180° swing is less than 1.5 s. The angular velocity in the plane of the target canal during particle repositioning manoeuvres may also affect particle movement [Furuya et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…So, if the 180° swing is performed quickly enough, then the effect on the posterior canal can be equivalent to a slow backward rotation. The success of the Semont manoeuvre therapy for BPPV is known to depend critically on the speed of the 180° whole-body swing [Radtke et al, 2004]. Analyses of the accelerations acting on the SCC during the Semont manoeuvre suggest that the optimum duration of the 180° swing is less than 1.5 s. The angular velocity in the plane of the target canal during particle repositioning manoeuvres may also affect particle movement [Furuya et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that patients can self-treat BPPV, although this was tested after patients were provided with illustrations and in-person instructions by an expert. [13][14][15] Effective videos could also be used by providers either as the primary prescription for patients with BPPV or as a reference to patients experiencing a recurrence. 13,14,16 Videos could also serve as a reminder to providers about the maneuver at the time of a patient encounter.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Effective videos could also be used by providers either as the primary prescription for patients with BPPV or as a reference to patients experiencing a recurrence. 13,14,16 Videos could also serve as a reminder to providers about the maneuver at the time of a patient encounter. 17 This could be accomplished, for example, by including the videos in the electronic medical record.…”
Section: Discussionmentioning
confidence: 99%
“…1 The Epley particle repositioning maneuver (PRM) has proven to be a fast, safe, and effective treatment for BPPV. 2,3 However, studies show that treatment success was only 34% after a single treatment when administered by family physicians, compared with the 67-89% success when administered by specialists. 2,4 The purpose of our study was to determine whether the use of an iPhone application that assists the user in the performance of the PRM had any significant impact on the overall correctness of the performed PRM.…”
Section: Tions Otolaryngologymentioning
confidence: 99%